Hepatic Glycogen Metabolism in Type 1 Diabetes After Long-Term Near Normoglycemia - BISCHOF, Martin G; BERNROIDER, Elisabeth; KRSSAK, Martin; KREBS, Michael; STINGL, Harald; NOWOTNY, Peter; CHUNLIN YU; SHULMAN, Gerald I; WALDHÄUSL, Werner; RODEN, Michael (Diabetes (New York, N.Y.), 2002)
Hepatic Glycogen Metabolism in Type 1 Diabetes After Long-Term Near Normoglycemia Martin G. Bischof 1 , Elisabeth Bernroider 1 , Martin Krssak 1 , Michael Krebs 1 , Harald Stingl 1 , Peter Nowotny 1 , Chunlin Yu 2 , Gerald I. Shulman 2 , Werner Waldhäusl 1 and Michael Roden 1 1 Division of Endocrinology and Metabolism, Department of Internal Medicine III, University of Vienna Medical School, Vienna, Austria 2 Howard Hughes Medical Institute, Department of Internal Medicine, Yale University School of Medicine, New Haven, Connecticut Abstract We tested the impact of long-term near normoglycemia (HbA 1c <7% for >1 year) on glycogen metabolism in seven type 1 diabetic and seven matched nondiabetic subjects after a mixed meal. Glycemic profiles (6.2 ± 0.10 vs. 5.9 ± 0.07 mmol/l; P < 0.05) of diabetic patients were approximated to that of nondiabetic subjects by variable insulin infusion. Rates of hepatic glycogen synthesis and breakdown were calculated from the glycogen concentration time curves between 7:30 p . m . and 8:00 a.m . using in vivo 13 C nuclear magnetic resonance spectroscopy. Glucose production was determined with d -[6,6- 2 H 2 ]glucose, and the hepatic uridine-diphosphate glucose pool was sampled with acetaminophen. Glycogen synthesis and breakdown as well as glucose production were identical in diabetic and healthy subjects: 7.3 ± 0.9 vs. 7.1 ± 0.7, 4.2 ± 0.5 vs. 3.8 ± 0.3, and 8.7 ± 0.5 vs. 8.4 ± 0.7 μmol · kg −1 · min −1 , respectively. Although portal vein insulin concentrations were doubled, the flux through the indirect pathway of glycogen synthesis remained higher in type 1 diabetic subjects: ∼70 vs. ∼50%; P < 0.05. In conclusion, combined long- and short-term intensified insulin substitution normalizes rates of hepatic glycogen synthesis but not the contribution of gluconeogenesis to glycogen synthesis in type 1 diabetes. Footnotes Address correspondence and reprint requests to Michael Roden, MD, Division of Endocrinology and Metabolism, Department of Internal Medicine III, University of Vienna Medical School, Waehringer Guertel 18-20, A-1090 Vienna, Austria. E-mail: michael.rodenatakh-wien.ac.at . Received for publication 24 July 2001 and accepted in revised form 25 October 2001. M.G.B. and E.B. contributed equally to this study. CV, coefficient of variation; EGP, endogenous glucose production; FFA, free fatty acid; HPLC, high-performance liquid chromatography; MPE, mol percent enrichment; NMR, nuclear magnetic resonance; PP-1, protein phosphorylase-1; RIA, radioimmunoassay.